Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2500/aap.2009.30.3294
|View full text |Cite
|
Sign up to set email alerts
|

Sesame allergy: Role of specific IgE and skin-prick testing in predicting food challenge results

Abstract: INTRODUCTIONSesame seed is an emerging food allergen in the U.S. pediatric population as it becomes more common in the American diet. A recent systematic review of seed allergies described a prevalence of < 1% for sesame allergy as defined by a positive food challenge.1 It has been reported that most patients have sesame allergy before the age of 2 and about 20% of children with clinical allergy eventually develop tolerance.2 Another study described 9 of 30 children (30%) developing tolerance at an average age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 13 publications
(20 reference statements)
4
32
1
1
Order By: Relevance
“…Similar to SPT, studies on sesame-sIgE showed inconsistent findings (62,90,92). In one study, 50 kUa/l had an 86% positive predictive value (92).…”
Section: Serum Specific Ige Levelmentioning
confidence: 86%
See 2 more Smart Citations
“…Similar to SPT, studies on sesame-sIgE showed inconsistent findings (62,90,92). In one study, 50 kUa/l had an 86% positive predictive value (92).…”
Section: Serum Specific Ige Levelmentioning
confidence: 86%
“…Similar to SPT, studies on sesame-sIgE showed inconsistent findings (62,90,92). In one study, 50 kUa/l had an 86% positive predictive value (92). In a study of 92 patients with sesame hypersensitivity based on positive challenge test or convincing history, the authors reported that a serum level of 3.96 kUa/l to the sesame allergen rSes i 1 had 85.7% sensitivity and 86.1% specificity (96).…”
Section: Serum Specific Ige Levelmentioning
confidence: 86%
See 1 more Smart Citation
“…Unlike eggs and milk, SFAbelongs to the group of foods, such as fish and peanuts that have a low rate of tolerance development (1,3). SFA is mainly acquired by contact and ingestion, but there are a few cases reporting sensitisation by inhalation (4)(5).…”
mentioning
confidence: 99%
“…The gold standard to confirm food allergy is a classical food challenge. In fact, in the case of sesame allergy, skin prick tests (SPT) and specific IgEs have not been established as good predictors oftrue allergy (1,3).…”
mentioning
confidence: 99%